Influences of cardiac motion on computed tomography-guided biopsy of lung nodules located near the heart. Issue 46 (November 2017) - Hsu, Li-Sheng; Chen, Chien-Wei; Chang, Chia-Hao; Liao, Chien-Han; Hsu, Sheng-Lung; Lin, Wei-Ming
Abstract : Abstract: Computed tomography (CT)-guided lung biopsy of nodules located near the heart may be associated with potential complications. To understand the influences of cardiac motion on lung parenchyma during biopsy, we processed the cardiac phase images of coronary CT angiography (CCTA) and noticed shifts in mediastinum lung margin (MLM) at different zones. Thirty eight CCTA (27 men and 11 women) were retrospectively evaluated. Image processing was done with Fiji (an open source Java image processing program by Fiji contributors) using 10% to 90% phase images of CCTA; and tissue displacement (MLM shift) was shown on the resulting images. The participants were 58.29 ± 9.87 years old; their height was 166.32 ± 7.57 cm while their weight was 74.18 ± 13.59 kg. The mean values of MLM shifts in Zones 1 to 9 ranged from 1.98 to 7.76 mm. Large MLM shifts were observed in the free wall of the left ventricle (LV). MLM shift of the upper free wall of the LV was 6.98 ± 1.99 mm and that of the lower free wall of the LV was 7.76 ± 3.26 mm. The largest MLM shift among all patients was 16.05 mm, found in the lower free wall of the LV. The age factor had a weak positive correlation with the wall of the pulmonary artery ( r  = 0.350, P  = .031) and that of the right atrial appendage ( r  = 0.418, P  = .009). In contrast, a weak negative correlation of age factor was observed with the lower free wall of the LV ( r  = −0.336, P  = .039). In conclusion, we suggest that physicians observe caution when performing lung biopsy if the distance between the lung lesion and the MLM is 1 to 2 cm. CT-guided lung biopsy should be avoided if the distance is <1 cm. Physicians should pay special attention to lung lesions near the LV.